Advances in Optical Communication - Das, Narottam (IntechOpen, 2014)
High-speed optical communication is very much useful in telecommunication systems, data processing and networking. It consists of a transmitter that encodes a message into an optical signal, a channel that carries this optical signal to its desired destination, and a receiver that reproduces the message from the received optical signal. It presents up to date results on communication systems, along with the explanations of their relevance, from leading researchers in this field. The chapters of this book cover general concepts of high-speed optical communication, optical devices used optical communication, and optical communication systems. In recent years, optical devices and other enhanced signal processing functions are also considered in depth for high-speed optical communications systems. Commonly used optical devices are light emitting diodes and photodetectors. This book is targeted at research, development and design engineers from the teams in manufacturing industry, academia and telecommunication industries.